Implementasi Kurikulum 2013: Pengaruhnya Terhadap Manajemen Dan Kualitas Pembelajaran - Fiolinda Febriana; Gladis Aprilia Rahayu; Hendri Budi Utama; Merika Setiawati (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This article examines the impact of the implementation of the 2013 Curriculum (K-13) on the management and quality of learning in schools. K-13, introduced in 2013/2014, emphasizes a scientific approach and aims to balance soft skills and hard skills, including attitudes, skills, and knowledge, through student-centered and authentic learning. Effective implementation requires systematic management involving planning, implementation, control, and evaluation, as well as synergistic collaboration between principals and teachers. However, its implementation faces challenges such as limited teacher training, disparity in facilities, lack of a comprehensive monitoring and evaluation system, and difficulty in student adaptation. Nevertheless, the implementation of K-13 shows a positive and significant influence on the management and quality of learning, encouraging a more structured, innovative, and competency-oriented process. Success depends on strengthening teacher capacity, equalizing facilities, and actively involving all stakeholders to achieve the curriculum's goals in producing a productive, creative, innovative, and character-based generation.